(untitled) (Latakia University Journal -Medical Sciences Series, 2024)
Introduction: Staphylococcus aureus has emerged as one of the most important human pathogens and has been leading cause of hospital- and community-acquired infections. MRSA strains pose a major threat to hospital patients because these bacteria may be transmitted by asymptomatic carriers of medical staff working in the hospital. MRSA carrying mecA gene is resistant to most beta-lactam antibiotics. In 2007, a new strain of Staphylococcus aureus containing a gene similar to mecA( mecC) was found in England, leading to diagnostic problems. Accurate and rapid detection of MRSA among health personnel is necessary for prevention and determining effective treatment.Objective: To detect the mecA and mecC genes among methicillin-resistant isolates of Staphylococcus aureus taken from the nasal carriers of medical staff working in the intensive care unit at Tishreen University Hospital to determine prevalence of MRSA in our hospital and limit it to reduce the material and moral burden of infection borne by health authorities and patients.Research materials and methods: A cross-sectional descriptive study was conducted in the microbiology laboratory at Tishreen University Hospital - Latakia - Syria and the laboratory of Department of Molecular Biology and Biotechnology at the Syrian Atomic Energy Commission - Damascus. 60 nasal swabs were collected from health personnel working in the intensive care unit at Tishreen Hospital. University. Characterization of bacterial strains for detection of Staphylococcus aureus and detection of MRSA was performed using Cefoxitin by disk diffusion method. The presence of mecA gene and the absence of mecC was confirmed by performing a mutiplexPCR assay Results: Among 60 nasal swabs taken from health staff working in the intensive care unit at Tishreen University Hospital, there were 24 samples diagnosed as Staphylococcus aureus (40%), and among them there were 20 samples MRSA (83.3%) based on resistance to cefoxitin. 20 mecA positive MRSA samples were 100%, while all samples were mecC negative.